From Bench to Bed: Bridging from Informatics Theory to Practice - Lehmann, C. U.; Haux, R. (Methods of Information in Medicine, 2014)
Background: In 2009, the journal Applied Clinical Informatics (ACI) commenced publication. Focused on applications in clinical informatics, ACI was intended to be a companion journal to Methods of Information in Medicine (MIM). Both journals are official journals of IMIA, the International Medical Informatics Association.Objectives: To explore, after five years, which congruencies and interdependencies exist in publications of these journals and to determine if gaps exist. To achieve this goal, major topics discussed in ACI and in MIM had to be analysed. Finally, we wanted to explore, whether the intention of publishing these companion journals to provide an information bridge from informatics theory to informatics practice and from practice to theory could be supported by this model. In this manuscript we will report on congruencies and interdependencies from practise to theory and on major topis in ACI. Further results will be reported in a second paper.Methods: Retrospective, prolective observational study on recent publications of ACI and MIM. All publications of the years 2012 and 2013 from these journals were indexed and analysed.Results: Hundred and ninety-six publications have been analysed (87 ACI, 109 MIM). In ACI publications addressed care coordination, shared decision support, and provider communication in its importance for complex patient care and safety and quality. Other major themes included improving clinical documentation quality and efficiency, effectiveness of clinical decision support and alerts, implementation of health information technology systems including discussion of failures and succeses. An emerging topic in the years analyzed was a focus on health information technology to predict and prevent hospital admissions and managing population health including the application of mobile health technology. Congruencies between journals could be found in themes, but with different focus in its contents. Interdependencies from practise to theory found in these publications, were only limited.Conclusions: Bridging from informatics theory to practise and vice versa remains a major component of successful research and practise as well as a major challenge.
Keywords: Biomedical informatics; health informatics; clinical informatics; medical informatics; serial publications